2020
DOI: 10.1021/acsami.9b22725
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Recyclable Surface-Enhanced Raman Scattering-Based Detection of Multicomponent Pesticide Residues on Fruits and Vegetables by the Flower-like MoS2@Ag Hybrid Substrate

Abstract: Pesticides, extensively used in agriculture production, have received enormous attention because of their potential threats to the environment and human health. Hence, in this study, a kind of highly sensitive and stable hybrid surface-enhanced Raman scattering (SERS)-active substrates constructed with flower-like two-dimensional molybdenum sulfide and Ag (MoS2@Ag) has been developed, and then the above substrate was sequentially utilized in the recyclable detection of pesticide residues on several kinds of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(58 citation statements)
references
References 54 publications
1
57
0
Order By: Relevance
“…The images in the "Regeneration" panel were reproduced with permission from ref. 73, copyright 2020 American Chemical Society, ref. 74 copyright 2016 The Royal Society of Chemistry and ref.…”
Section: Flexible Sers Substrates For the Analysis Of Chemical Residues On Complex Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The images in the "Regeneration" panel were reproduced with permission from ref. 73, copyright 2020 American Chemical Society, ref. 74 copyright 2016 The Royal Society of Chemistry and ref.…”
Section: Flexible Sers Substrates For the Analysis Of Chemical Residues On Complex Surfacesmentioning
confidence: 99%
“…x , have been used to construct SERS substrates, which can be regenerated with UV irradiation. 73,[236][237][238] However, the prolonged regeneration process along with the requirement for special irradiation sources make these substrates less ideal in practice. This has led to the development of visible-lightinduced self-cleaning SERS substrates, which are potentially more sustainable and often offer faster regeneration speed compared to their UV-excited counterparts.…”
Section: Photocatalytic Regenerationmentioning
confidence: 99%
“…In theory, SERS can detect multiple pesticides by the specific and identifiable peaks of each pesticide. However, SERS technique fails to detect more than five pesticides synchronously each time in the practical application [135,136], which probably results from the competitive adsorption of substrates by various pesticides molecules. The affinity of pesticides molecules to substrate varies from the structure group of pesticides.…”
Section: How To Choose Suitable Substrate For Sers Detection Of Pesticidesmentioning
confidence: 99%
“…[ 19 ] On this basis, it is observed that Ag NPs and MoO x form a more robust heterojunction after electrical programming; however, band edge alignment between Ag NPs and MoO x reveals that they form an Ohmic contact kind of heterojunction, resulting in little help in promoting the charge transfer (see Figure S2, Supporting Information). [ 20 ] As shown in Figure S1, Supporting Information, the chemical enhancement from the pure MoO x is also insignificant when compared to the total SERS enhancement; thus it can be inferred that the SERS enhancement of the of the MoO x /Ag NP hybrids is mainly contributed by the EM from Ag NPs. Therefore, finite‐difference time‐domain (FDTD) simulation was performed to investigate the Ag NPs’ surface electromagnetic field.…”
Section: Figurementioning
confidence: 99%